‘Benevolent Supremacy’: The Biblical Epic at theDawn of the American Century, 1947-1960: 1960-1947 - McAlister, Melani (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2009)
This article suggests that both the foreign policy positions of the United States during the Cold War Era, and the biblical epics produced in Hollywood at that same time, were part of the same political and cultural discourse constructing the nature of U.S. power in the Middle East in the postwar period. The author exposes the intricate connections between the representation of American ’benevolent supremacy’ in world affairs in National Security Council document 68 (1950), and the anti-totalitarian, anti-colonial narratives of biblical epics as Quo Vadis (1952) and The Ten Commandments (1956). The article demonstrates how foreign policy documents and popular cultural texts constructed the Cold War as a global contest of values, with U.S.-dominated liberty as the key to freedom from slavery and sexual subordination, and to the proper domestic order